Presidents, Parties And Policy Competition - BENOIT, KENNETH (My University, 2009)
Presidential systems present a unique possibility for spatial competition between elected political agents, since presidents may represent different policy positions than the parties to which they belong. Previous research, however, has lacked a firm empirical basis on which to measure these differences. We remedy this situation, providing independent estimates of positions and saliencies for presidents and parties on multiple policy dimensions in 18 Latin American countries, from original expert survey data. Our results offer strong evidence that positioning on nearly all political issues neatly reduces to a single dimension of left-right contestation. Furthermore, contrasting differences between the positioning of presidents and their own parties, we show that presidents tend to position themselves independently of their parties more in bicameral and proportional representation systems, when they differ in the importance they assign to a given policy dimension, and when elections with legislatures are nonconcurrent.
PUBLISHED
Keywords: Political Science